2016
DOI: 10.2147/tcrm.s109785
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic indicators for failed nonsurgical reduction of intussusception

Abstract: PurposeTo identify the risk factors for failure of nonsurgical reduction of intussusception.MethodsData from intussusception patients who were treated with nonsurgical reduction in Chiang Mai University Hospital and Siriraj Hospital between January 2006 and December 2012 were collected. Patients aged 0–15 years and without contraindications (peritonitis, abdominal X-ray signs of perforation, and/or hemodynamic instability) were included for nonsurgical reduction. The success and failure groups were divided acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
34
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 21 publications
8
34
2
Order By: Relevance
“…Literature shows that rectal bleeding decreases the success rate of reduction (18,19,(23)(24)(25)(26)(27)(28)(29). Rectal bleeding is an indicator of edema and circulatory impairment and is seen in 60% of the patients with intussusceptions (3).…”
Section: Discussionmentioning
confidence: 99%
“…Literature shows that rectal bleeding decreases the success rate of reduction (18,19,(23)(24)(25)(26)(27)(28)(29). Rectal bleeding is an indicator of edema and circulatory impairment and is seen in 60% of the patients with intussusceptions (3).…”
Section: Discussionmentioning
confidence: 99%
“…The CMUI scoring system was created by Khorana et al from CMU, Thailand,10 with an aim to be used as a predictor of failure in non-surgical treatment of intussusception. The scoring system consists of 10 items, that is, body weight less than 12 kg, duration of symptoms more than 48 hours, vomiting, rectal bleeding, abdominal distension, temperature more than 37.8°C, palpable mass, location, poor ultrasound signs, and method of reduction.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, bypassing any attempt at non-surgical management in cases with a poor probability of successful reduction could also avoid complications caused by prolonged strangulation 9. Various clinical and radiologic factors have been reported as being associated with failure of non-surgical management for intussusception, which can be subcategorized into four groups: demographic factors, clinical symptoms, physical examination factors and imaging factors 6 10. Regarding demographic factors and clinical symptoms, younger age, longer duration of abdominal pain, rectal bleeding, presence of diarrhea, abdominal distension, and dehydration or vomiting are the main unfavorable factors.…”
Section: Introductionmentioning
confidence: 99%
“… 9 The second study reported the prognostic indicators of failed operative reduction. 8 This was the third study that used ten prognostic factors for failed nonsurgical reduction derived from the second study.…”
Section: Methodsmentioning
confidence: 99%
“…Our earlier series studied the prognosis indicators for failed reduction and found that body weight <12 kg, duration of symptoms >3 days, vomiting, rectal bleeding, abdominal distension, temperature >37.8°C, palpable abdominal mass, location of mass on the left side, ultrasound showing poor prognostic signs, and the method of reduction (hydrostatic over pneumatic) were the factors. 8 …”
Section: Introductionmentioning
confidence: 99%